2012
DOI: 10.1111/j.1744-313x.2012.01135.x
|View full text |Cite
|
Sign up to set email alerts
|

Sequence characterization of river buffalo Toll‐like receptor genes 1–10 reveals distinct relationship with cattle and sheep

Abstract: The present study was undertaken to characterize the full-length transcripts of Toll-like receptor (TLR) genes 1-10 of river buffalo. The conceptualized amino acid identity of bubaline TLRs ranged between 86% to 100% with ruminants, while it ranged between 45% to 91% with other vertebrate species. Simple modular architecture tool (SMART) analysis revealed the presence of TIR domains and varying numbers of leucine-rich repeat motifs in all the buffalo TLRs. With respect to TIR domains, TLRs 1, 2 and 3 of river … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 26 publications
8
12
0
Order By: Relevance
“…Specifically, the mRNA levels of TLR2 and TLR4 increase in endometritis infection of bacterial origin (Ozinsky et al, 2000;Goldammer et al, 2004;Azawi et al, 2008;Davies et al, 2008). With the agreement of these data, we detected overexpression of all five examined TLR genes, particularly TLR2 (26.4 fold) and TLR4 (12.4 fold), in infected uterine tissues with endometritis compared to the uninfected ones.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…Specifically, the mRNA levels of TLR2 and TLR4 increase in endometritis infection of bacterial origin (Ozinsky et al, 2000;Goldammer et al, 2004;Azawi et al, 2008;Davies et al, 2008). With the agreement of these data, we detected overexpression of all five examined TLR genes, particularly TLR2 (26.4 fold) and TLR4 (12.4 fold), in infected uterine tissues with endometritis compared to the uninfected ones.…”
Section: Discussionsupporting
confidence: 84%
“…The number and structure of LRRs of TLRs have a significant effect on the function of pathogen recognition receptor system among species (Kumar et al, 2009;Dubey et al, 2013). Peter et al (2009) reported that deletion of LRR motif leads to loss of functional integrity of the ligand-binding domain of murine TLRs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are ~ 13 known mammalian TLRs: TLRs 1-13 in murine animals (Hopkins and Sriskandan 2005), TLRs 1-10 (except TLR7) in rabbits (Chen et al 2014), TLRs 1-10 in ruminants (Menzies and Ingham 2006;Chang et al 2009;Raja et al 2011), and TLRs 1-10 in humans (Rock et al 1998;Werling and Coffey 2007). The full sequence of TLR genes has been discovered in humans, monkeys, mice, rats, rabbits, pigs, cattle, sheep, goats, horses and chicken (Rock et al 1998;Yilmaz et al 2005 genes of Indian river type NR buffaloes have been cloned and sequenced (Dubey et al 2013). However, TLR gene sequences of swamp-type buffaloes from GX region in China have not been evaluated.…”
Section: Introductionmentioning
confidence: 99%